2003
DOI: 10.1002/ajim.10268
|View full text |Cite
|
Sign up to set email alerts
|

The Drake Health Registry Study: Cause‐specific mortality experience of workers potentially exposed to beta‐naphthylamine

Abstract: Bladder cancer risk remains highly elevated among Drake/Kilsdonk workers and appears to be causally related to past BNA exposure. While lifestyle and behavioral risk factors may explain some of the mortality excesses for non-urological cancers, the possibility remains that BNA exposure may have also played a role in these and other observed cancer excesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Bladder cancer (49,216,217,218,219) Bladder carcinomas in rats, angiosarcoma, hepatocellular tumors and bladder carcinoma in mice; intestinal tumors, liver sarcoma, mammary tumors, uterus in rats; bronchioalveolar adenoma in mice; uterus carcinomas in rat; bladder carcinomas in rabbits bladder papilloma and bladder carcinoma in dogs (193,220,222,223,224,225,226,227) 2-Naphthylamine Bladder cancer (41,63,156,162,165,169,174,209,228,229,230,231,232,233,234,235,236,237) Liver cholangioma, hepatomas in mice, bladder papilloma in rats, bladder carcinoma and hepatoma in hamster, papilloma and carcinoma of bladder in dog (108, 192, 236. 237, 238, 239, 240, 241,242, 243, 244, 245, 246, 247, 248) o-Toluidine Bladder cancer (160,239,240,249,20,251) Hepatocellular adenoma, carcinomas in mice, fibromas of the skin, spleen mammary fibroadenoma, and sarcoma of rat, fibrosarcoma or osteosarcoma of multiple organs of rat (76,252,253) 4-Chloro-o-Toluidine Bladder cancer (254) Haemangiosma and haemangiosarcoma...…”
Section: -Aminobiphenylmentioning
confidence: 99%
“…Bladder cancer (49,216,217,218,219) Bladder carcinomas in rats, angiosarcoma, hepatocellular tumors and bladder carcinoma in mice; intestinal tumors, liver sarcoma, mammary tumors, uterus in rats; bronchioalveolar adenoma in mice; uterus carcinomas in rat; bladder carcinomas in rabbits bladder papilloma and bladder carcinoma in dogs (193,220,222,223,224,225,226,227) 2-Naphthylamine Bladder cancer (41,63,156,162,165,169,174,209,228,229,230,231,232,233,234,235,236,237) Liver cholangioma, hepatomas in mice, bladder papilloma in rats, bladder carcinoma and hepatoma in hamster, papilloma and carcinoma of bladder in dog (108, 192, 236. 237, 238, 239, 240, 241,242, 243, 244, 245, 246, 247, 248) o-Toluidine Bladder cancer (160,239,240,249,20,251) Hepatocellular adenoma, carcinomas in mice, fibromas of the skin, spleen mammary fibroadenoma, and sarcoma of rat, fibrosarcoma or osteosarcoma of multiple organs of rat (76,252,253) 4-Chloro-o-Toluidine Bladder cancer (254) Haemangiosma and haemangiosarcoma...…”
Section: -Aminobiphenylmentioning
confidence: 99%
“…65 Although four studies obtained information on cigarette smoking, two of them calculated smoking-adjusted risk only for bladder cancer, 36 , 38 and one of them had incomplete tobacco smoking data (lacking in about one third of cohort members). 10 Only one study 11 presented an effect estimate for lung cancer risk from a multivariate model; the relative risk for lung cancer incidence after adjustment for age at first exposure, smoking status, and other occupational co-exposure was 3.02 (95% CI, 0.84–10.93) for long duration of employment compared with the short duration group. Lack of adjustment for smoking might lead to overestimation of the association between lung cancer and exposure to BZ/BNA.…”
Section: Discussionmentioning
confidence: 99%
“…811 However, most studies 810 failed to confirm a positive dose-response relationship between BZ/BNA exposure and the risk for lung cancer due to an insufficient number of cases. The inadequate statistical evidence of those individual studies would not allow for a proper interpretation of the effect of BZ and/or BNA in regards to lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Eastern European countries tended to be geographically clustered in this study. Pisani et al (1999), Ginter (2000), Levi et al (1999) and Karimian-Teherani et al (2001) Lei et al, 1996;Zaridze et al, 2000;Jedrychowski et al, 1999;Chow et al, 1999), but also occupational factors (Bulbulyan et al, 1995(Bulbulyan et al, , 1996Gustavsson et al, 1998;Cassidy et al, 2003;Golka et al, 2003) and environmental pollution (Sandor et al, 2001;Gulis et al, 2002;Perera et al, 1992;Shields et al, 1995;Engholm et al, 1996;Choi et al, 1997;Simonato et al, 2000;Franceschi et al, 2003) were found to be possible risk factors for malignant neoplasms. The wide health gap found was due to these unhealthy risk factors (Nanda et al, 1993).…”
Section: Social and Environmentalmentioning
confidence: 99%